2020
DOI: 10.1007/s00415-020-10177-y
|View full text |Cite
|
Sign up to set email alerts
|

The gait disorder in primary orthostatic tremor

Abstract: Objective To uncover possible impairments of walking and dynamic postural stability in patients with primary orthostatic tremor (OT). Methods Spatiotemporal gait characteristics were quantified in 18 patients with primary OT (mean age 70.5 ± 5.9 years, 10 females) and 18 age-matched healthy controls. One-third of patients reported disease-related fall events. Walking performance was assessed on a pressure-sensitive carpet under seven condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…We aimed to determine the effect of a loss of peripheral vestibular function by comparing the spatiotemporal gait parameters and their step-to-step variability between BVP-patients and healthy controls during overground walking at preferred walking speed. We hypothesize that, in accordance with previous studies 24 , 26 , 27 , 33 , 34 , BVP-patients will show an increased gait variability during walking. Additionally, we also examined the interaction between the spatiotemporal gait parameters and MoS in BVP as compared to the healthy controls.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…We aimed to determine the effect of a loss of peripheral vestibular function by comparing the spatiotemporal gait parameters and their step-to-step variability between BVP-patients and healthy controls during overground walking at preferred walking speed. We hypothesize that, in accordance with previous studies 24 , 26 , 27 , 33 , 34 , BVP-patients will show an increased gait variability during walking. Additionally, we also examined the interaction between the spatiotemporal gait parameters and MoS in BVP as compared to the healthy controls.…”
Section: Introductionsupporting
confidence: 84%
“…This could indicate a shift from a sensory feedback-driven control of balance to a more feedforward control of balance, as has been suggested before 22 , 35 37 . In addition, it has been shown that during slow walking speeds, the variability of most parameters is highest in BVP-patients 24 , 26 , 27 , 34 , 38 . The reason for this could be an increased need for sensory feedback at slower walking speeds in general, as passive dynamics play a smaller role in stabilising the body during this condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas initial reports describe the absence of ataxia and bradykinesia in POT, several recent reports indicate the potential presence of cerebellar ataxia. 10 , 11 , 12 , 13 , 14 , 15 These mainly comprise of features of gait such as reduced step length and increased step width, but also a certain degree of appendicular ataxia has been suggested. These observations are contradicted by case series demonstrating only very rare occurrence of ataxia.…”
mentioning
confidence: 99%